2004
DOI: 10.1021/jo0356558
|View full text |Cite
|
Sign up to set email alerts
|

Remarkably Facile Solvolyses of Triflates via Carbocationic Processes in Dimethyl Sulfoxide

Abstract: A number of triflates have been shown to undergo clean pseudo-first-order solvolysis reactions in DMSO-d(6) to give products derived from carbocationic intermediates. Thus, t-BuCH(OTf)CO-t-Bu (5) and t-BuCH(2)OTf (9) react readily in DMSO-d(6) at 25 degrees C to give a rearranged oxosulfonium salts, and subsequent alkene products where methyl migration to the incipient cationic center occurs. t-BuCH(OTf)CO(2)CH(3) (14) gives analogous rearranged products, and 1-methylcyclopropyl triflate (21) gives a ring-open… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 32 publications
2
8
0
Order By: Relevance
“…We assume that it corresponds to a sulfonium intermediate, formed after the nucleophilic ring opening of the activated epoxide by DMSO, namely trans ‐2‐[(dimethylsulfonio)oxy]cyclohexanolate. The presence of the sulfonium intermediate in the reaction mixture is consistent with previous studies on the acid‐catalysed oxidation of epoxides by DMSO (Figure 2) described by Swern et al,16 and has also been reported in the solvolysis of triflates by DMSO 18…”
Section: Resultssupporting
confidence: 91%
“…We assume that it corresponds to a sulfonium intermediate, formed after the nucleophilic ring opening of the activated epoxide by DMSO, namely trans ‐2‐[(dimethylsulfonio)oxy]cyclohexanolate. The presence of the sulfonium intermediate in the reaction mixture is consistent with previous studies on the acid‐catalysed oxidation of epoxides by DMSO (Figure 2) described by Swern et al,16 and has also been reported in the solvolysis of triflates by DMSO 18…”
Section: Resultssupporting
confidence: 91%
“…We were unable to isolate or spectroscopically detect the intermediate I′, but the existence of the oxosulfonium ion was confirmed earlier. 40,41 The similar was observed in DMSOassisted solvolysis of triflates in which the intermediacy of oxosulfonium ion was proposed. 42 By using DFT methods (B3LYP and M06L), we located the structure I′ as a genuine minimum at the corresponding potential energy surface.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Certain triflates were especially prone to give carbocation chemistry in DMSO. 3 We are therefore interested in the ability of novel or unusual solvents to support carbocationic intermediates.…”
Section: Introductionmentioning
confidence: 99%